U-Limb: A multi-modal, multi-center database on arm motion control in healthy and post-stroke conditions. Issue 6 (18th June 2021) - Averta, Giuseppe; Barontini, Federica; Catrambone, Vincenzo; Haddadin, Sami; Handjaras, Giacomo; Held, Jeremia P O; Hu, Tingli; Jakubowitz, Eike; Kanzler, Christoph M; Kühn, Johannes; Lambercy, Olivier; Leo, Andrea; et al.
Abstract: Background: Shedding light on the neuroscientific mechanisms of human upper limb motor control, in both healthy and disease conditions (e.g., after a stroke), can help to devise effective tools for a quantitative evaluation of the impaired conditions, and to properly inform the rehabilitative process. Furthermore, the design and control of mechatronic devices can also benefit from such neuroscientific outcomes, with important implications for assistive and rehabilitation robotics and advanced human-machine interaction. To reach these goals, we believe that an exhaustive data collection on human behavior is a mandatory step. For this reason, we release U-Limb, a large, multi-modal, multi-center data collection on human upper limb movements, with the aim of fostering trans-disciplinary cross-fertilization. Contribution: This collection of signals consists of data from 91 able-bodied and 65 post-stroke participants and is organized at 3 levels: (i) upper limb daily living activities, during which kinematic and physiological signals (electromyography, electro-encephalography, and electrocardiography) were recorded; (ii) force-kinematic behavior during precise manipulation tasks with a haptic device; and (iii) brain activity during hand control using functional magnetic resonance imaging.